2007
DOI: 10.1597/06-047.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bone Resorption after Secondary Alveolar Bone Grafting Using Three-Dimensional Computed Tomography: A Three-Year Study

Abstract: Radiographic scales based on orthopantomography only evaluate the vertical dimension of the transplants. This study, however, showed that bone resorption in the transversal dimension is clearly underestimated with conventional two-dimensional radiographs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
0
14

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(141 citation statements)
references
References 28 publications
6
119
0
14
Order By: Relevance
“…8 Moreover, 2 dimensional (2D) imaging is too limited in volume analysis due to the superimposition of the adjacent anatomical structures, distortions and enlargements. [9][10][11][12] Therefore the use of CT in the assessment of the alveolar bone graft is recently widespread. 10,11,13,14 The common point of agreement between these studies is that the amount of bone loss is significantly higher than that shown by 2D imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Moreover, 2 dimensional (2D) imaging is too limited in volume analysis due to the superimposition of the adjacent anatomical structures, distortions and enlargements. [9][10][11][12] Therefore the use of CT in the assessment of the alveolar bone graft is recently widespread. 10,11,13,14 The common point of agreement between these studies is that the amount of bone loss is significantly higher than that shown by 2D imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The success rate of grafting in our patient was is in accordance with the results of Honma et al Several studies concerning postoperative bone volume measurements indicated higher bone resorption ratios than the present results especially 2 and 3 years after bone grafting procedure. 10,11,17 Closure of the alveolar defect with autogenous bone grafting, enabled the closure of the oronasal fistules, presentation of the arch integrity and eruption of the tooth in the cleft side. Therefore retromolar region where 3 rd molars…”
Section: Discussionmentioning
confidence: 99%
“…12 Once erupted the canines maintain the alveolar bone within the grafted region as without this functional stimulation, the bone rapidly resorbs. 15 Once the tooth is erupted through the graft then its periodontal support is adequate to allow orthodontic intervention and tooth movement. 16 Prior to the advent of secondary alveolar bone grafting (ABG) the aims of orthodontic treatment was limited to expansion and alignment.…”
Section: Methodsmentioning
confidence: 99%
“…In order to assess the changes in bone volume, 3D imaging is definitely necessary. (Feichtinger, Mossbock, & Karcher, 2007) The aim of this study is to evaluate the effect of gender on the postoperatively obtained new bone volume via the method of 3D volumetric analysis in the treatment of alveolar cleft with platelet-rich fibrine (PRF) application and iliac bone graft.…”
Section: Alveolar Cleft Iliac Bone Graft Gendermentioning
confidence: 99%